Recent development of magnetic sensor - Saleh, Akmal Muhaimin; Abdul Rahim, Ruzairi; Pusppanathan, Jaysuman; Md Yunos, Yusri (Penerbit UTHM, 2020)
With recent advancement of sensors development, many efforts have been made in improving technologies that can turn every measurable value in the environment into something meaningful at least that is the idea of transducers – a collection of devices that can convert physical quantities into electrical value. For instance, temperature sensor converts degree of hotness (temperature) into voltages, which in turn can be hooked on an electrical signal processing circuit to produce a thermo-controller. Various other types of transducer are available nowadays that can detect many elements, for examples ultrasonic sensor for distance, pressure sensors, proximity, infrared sensors and many others...